HUBUNGAN KECERDASAN EMOSIONAL (EQ) DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KIMIA SISWA SMA - Hafni Indriati Nasution; Ratna Sari Dewi; Hilda Junanda Br. Harahap (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract This Research intents to know wheather there is relation between emotional  intellegence and study motivation towards the result of studying chemistry sample that is being used is XI th grader of Setia Budi  Abadi Perbaungan High School terms 2013/2024 which consist of 52 students who are separated in to two class.Valid questionnaire is used to determine their emotional intelligences and study motivation. The 14 Questions for emotional intelligence and 13 questions for study motivation.While chemistry student learning outcome data obtained   from chemistry subject teacher.Data has been checked the normality by using liliefors test,for emotional intelligence obtained Lcount = 0,01149, where as for study motivation Lcount= 0,002167,and Ltable= 0,122866,with the result of that  Lcount> Ltable.Which means,the data distributed normally from the result of the hypotesis using multiple corelation test,show that there is positive relation between emotional intelligence and study motivation to chemistry student learning result with enough interpretation.Correlation’s significance is tested with F test at significance level of α= 0,05 with numerator dk 2 and denominator dk 49 show that Ftable= 3,19, while Fcount= 5,536645 (Fcount>F table) which means the relation between emotional  intelligence and study motivation with chemistry student learning result is real andabsolutely relevant statistically (significant). By counting the coefisien of determination gets the big impact of emotional intelligence and study motivation to wards chemistry student learning result is 18,23%. Keyword:Emotional Intellegence (EQ),Study Motivation,Result of studying